Soil-Subsurface Change Chemical Pollutant Impacts - Yaron, Bruno; Dror, Ishai; Berkowitz, Brian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book combines soil science, earth science, and environmental geochemistry, providing comprehensive background information for specialists interested in chemical-induced changes in the soil-subsurface system. Readers are introduced to the chemistry of contaminants that often disturb the natural soil-subsurface equilibrium as a result of human activity. While the soil-subsurface system has in many cases been affected by human impact, the effects of chemical contaminants on the actual matrix and properties have been largely neglected. The major focus of the book is on changes to the soil-subsurface matrix and properties caused by chemical pollution. By integrating results available in the literature, we observe that chemical pollutants may lead to the irreversible formation of a new soil-subsurface regime characterized by a matrix and properties different than those of the natural regime. In contrast to the geological time scales dictating natural changes to the matrix and properties of the soil-subsurface system, the time scale associated with chemical pollutant-induced changes is far shorter and extends over a (3z(Bhuman lifetime scale.(3y (BThe numerous examples presented in the book confirm that chemical contamination should be considered as an additional factor in the formation of a contemporary soil-subsurface regime that is different than that of the pristine system.s
Chemical Pollutants as a Factor of Soil-Subsurface Irreversible Transformation: An Introductory Discussion -- Soil-Subsurface Interrelated Matrix -- Properties and Behavior of Selected Inorganic and Organometallic Contaminants -- On the Retention and Transformation of Contaminants in Soil and the Subsurface -- Irreversible Alteration of Soil-Subsurface Matrix Induced by Contaminant Exchange Processes -- Irreversible Alteration of Soil-Subsurface Matrix Induced by Contaminant Binding -- Contaminant-Induced Irreversible Changes in Properties of the Soil-Subsurface Regime.
Keywords: Environmental sciences; Geochemistry; Environmental toxicology; Soil conservation; Environmental pollution; Environment; Terrestrial Pollution; Ecotoxicology; Geochemistry; Soil Science & Conservation